SEISMIC RECORDING ON DRIFTING ICEBERGS: CATCHING SEISMIC WAVES, TSUNAMIS AND STORMS FROM SUMATRA AND ELSEWHERE - Okal E.A.; MacAyeal D.R. (My University, 2006)
Under the Incorporated Research Institutions for Seismology (IRIS) Program for Array Seismic Studies of the Continental Lithosphere (PASSCAL) project SOUTHBERG, we have operated for the past three years a number of seismic stations on giant Antarctic icebergs parked or drifting slowly along the margins of the Ross Sea. The purpose of this deployment was to investigate in situ the characteristics and origin of high-frequency tremors emanating from inside the icebergs, tremors that previously had been detected in the far field as hydroacoustic T phases recorded in French Polynesia.